2019
DOI: 10.1088/2631-8695/ab4abf
|View full text |Cite
|
Sign up to set email alerts
|

A finite element analysis of a lightweight blast proof sandwich structure

Abstract: The objective of this study is to analyze the performance of a blast-proof composite material upon impact loading subjected under blast. The material that is currently being used for blast protection is armored steel. Although it has high strength and toughness its strength to weight ratio is low which limits the applications of armored steel. Hence to overcome this limitation a sandwich composite was considered as an alternative to steel for blast protection. The sandwich composite had the top layer as Cerami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Both the non-auxetic (No. [8][9][10][11][12][13][14][15][16][17] and the prismatic variants (No. [18][19][20][21], in contrast to the honeycomb cores, were primarily subjected to bending stress under the given load.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both the non-auxetic (No. [8][9][10][11][12][13][14][15][16][17] and the prismatic variants (No. [18][19][20][21], in contrast to the honeycomb cores, were primarily subjected to bending stress under the given load.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…For this reason, the present contribution puts a special focus on the blast resistance of lightweight structures. Numerous studies have demonstrated the improved performance of structural components based on sandwich-structured composites in the case of blast loading due to detonation processes (in water or air) compared to monolithic panels of the same weight [7][8][9][10]. This superiority is expressed both in the lower level of deflection with respect to the rear face and in the reduction in the forces transmitted to the substructure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation